2009
DOI: 10.1159/000230031
|View full text |Cite
|
Sign up to set email alerts
|

Pure Primary Prostatic Osteosarcoma Arising in a Non-Irradiated Prostate

Abstract: A 68-year-old man who initially presented with hematuria was found on prostate biopsy to have sarcoma of the prostate with osteogenic features. Radiological examination revealed a locally advanced pelvic mass involving the prostate, seminal vesicles, and rectal wall without metastatic disease. The patient underwent total pelvic exenteration with intraoperative radiotherapy. The tumor was composed of two nodules measuring 7.5 and 4.5 cm involving the prostate, both seminal vesicles, the bladder, rectum, and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A second search, with the same limiters, was conducted using the search terms “prostate” and “sarcomatoid carcinoma”. Twenty-seven papers were retrieved, only three of which involved ≥5 patients 10 , 11 , 35…”
Section: Discussionmentioning
confidence: 99%
“…A second search, with the same limiters, was conducted using the search terms “prostate” and “sarcomatoid carcinoma”. Twenty-seven papers were retrieved, only three of which involved ≥5 patients 10 , 11 , 35…”
Section: Discussionmentioning
confidence: 99%
“…Rabbani et al. 160 described an aggressive and lethal prostate tumour in a 68‐year‐old composed of undifferentiated pleomorphic spindle cells with osteoid formation and osteoclastic giant cells. Nishiyama et al.…”
Section: Miscellaneous Mesenchymal Tumours Of the Prostatementioning
confidence: 99%
“…However, there are sporadic reports of bone or cartilage forming tumours involving the prostate that were not carcinoma-associated. Rabbani et al 160 described an aggressive and lethal prostate tumour in a 68-year-old composed of undifferentiated pleomorphic spindle cells with osteoid formation and osteoclastic giant cells. Nishiyama et al 161 also reported an aggressive and lethal prostate tumour composed of pleomorphic cells with osteoid formation.…”
Section: Osteogenic and Chondrogenic Tumoursmentioning
confidence: 99%